Coexistence of psoriasis with bullous pemphigoid - Raghavendra Rao; Akash Gupta; Fousiya Yunis; Sripathi Handettu; Balachandran Chandrashekar (Wolters Kluwer Medknow Publications, 2012)
Psoriasis vulgaris and bullous pemphigoid (BP) represent two clinically well-characterized, chronic, inflammatory skin conditions. The concomitant occurrence of these two entities in a patient is rare. Here we report a 57-year-old male suffering from psoriasis vulgaris for 15 years on irregular medication who noticed eruption of blisters all over the body. We believe that this is the first case report of psoriasis vulgaris coexistent with bullous pemphigoid in Indian literature. Please check where you want bullous pemphigoid and where you want psoriasis pemphigoides.